Answer:
81
Step-by-step explanation:
i added it all
Hence the correct answer is C) -23
Further explanation:
We have to put the values of m and n into both expression first separately and then multiply the answers.
Given expressions are:
![Exp\ 1:3m-4n\\Exp\ 2: n^2-m](https://tex.z-dn.net/?f=Exp%5C%201%3A3m-4n%5C%5CExp%5C%202%3A%20n%5E2-m)
The values are:
![m=5\\n=-2](https://tex.z-dn.net/?f=m%3D5%5C%5Cn%3D-2)
Putting the values in expression 1:
![3m-4n\\=3(5)-4(-2)\\=15+8\\=23](https://tex.z-dn.net/?f=3m-4n%5C%5C%3D3%285%29-4%28-2%29%5C%5C%3D15%2B8%5C%5C%3D23)
Putting the values of m and n in second expression
![n^2-m\\=(-2)^2-5\\=4-5\\=-1](https://tex.z-dn.net/?f=n%5E2-m%5C%5C%3D%28-2%29%5E2-5%5C%5C%3D4-5%5C%5C%3D-1)
Multiplying both expressions:
![(3m-4n)(n^2-m)=23* (-1)=-23](https://tex.z-dn.net/?f=%283m-4n%29%28n%5E2-m%29%3D23%2A%20%28-1%29%3D-23)
Hence the correct answer is C) -23
Keywords: Polynomials, Putting values in expressions
Learn more about polynomials at:
#LearnwithBrainly
Answer:
0.08(50h)
Step-by-step explanation:
0.08(50h)+50h=
8/100(50h)+50h=
0.08(50h)+50h
It's 0.08 of 50h, so
0.08(50h)
We have the following equation:
2 (x-3) ^ 2 + 10 = 82
We must clear x.
We pass the constant terms to one side of the equation:
2 (x-3) ^ 2 = 82 - 10
2 (x-3) ^ 2 = 72
(x-3) ^ 2 = 72/2
(x-3) ^ 2 = 36
Square root to both members:
x-3 = +/- root (36)
x-3 = +/- 6
The solutions are:
x1 = 6 + 3 = 9
x2 = -6 + 3 = -3
Answer:
x1 = 9
x2 = -3
Answer:
i dont now
Step-by-step explanation:
inde man kona ka balo sorry